2009
DOI: 10.1016/j.trstmh.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections in HIV/AIDS patients presenting with diarrhoea in Jakarta, Indonesia

Abstract: We investigated the occurrence of intestinal parasites in Indonesian HIV/AIDS patients with chronic diarrhoea prior to administering antiretroviral therapy. The influence of age, CD4(+) cell count and season on parasite occurrence was also studied. In total, 318 unconcentrated stool samples were analysed using Lugol's iodine and modified acid fast staining to detect intestinal coccidia. Most samples (94.5%) were from males aged 21-40 years with CD4(+) counts < or = 50 cells/mm(3). Parasites were found in 84.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
66
7
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 22 publications
9
66
7
4
Order By: Relevance
“…The results indicated that the prevalence of intestinal parasitic infections in these patients was high. Studies from across the world on the intestinal parasites have reported high prevalence of these parasites in HIV-positive patients (11)(12)(13)(14), which is consistent with the present study. In a study in 2004 by Hailemariam et al in Ethiopia on 104 patients, it was found that of 78 HIV-positive patients, 41 patients (52.6%) and of 26 HIV-negative patients, 11 patients (42.32%) had gastrointestinal parasite infection; also multiple gastrointestinal parasite infections were common in these patients (15).…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that the prevalence of intestinal parasitic infections in these patients was high. Studies from across the world on the intestinal parasites have reported high prevalence of these parasites in HIV-positive patients (11)(12)(13)(14), which is consistent with the present study. In a study in 2004 by Hailemariam et al in Ethiopia on 104 patients, it was found that of 78 HIV-positive patients, 41 patients (52.6%) and of 26 HIV-negative patients, 11 patients (42.32%) had gastrointestinal parasite infection; also multiple gastrointestinal parasite infections were common in these patients (15).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, apart from the effects of HIV enteropathy, the presence of intestinal parasites is an important contributing factor to diarrhoea, which in the longer term could result in the wasting syndrome called "slim disease" [3,21]. In agreement with observations reported in previous studies [22,23], our investigation found that intestinal parasites associated with HIV were more likely encountered as the CD4 + count fell below 200 cells/μL, resulting in a higher prevalence of diarrhoea in this category of patients. As shown by Assefa et al [4], patients with severe immunodeficiency are more susceptible to acquire particular parasites and are also unable to clear established infections.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research has shown that patients can be co-infected with Cryptosporidium and parasites such as Blastocystis hominis, Giardia spp., Entamoeba histolytica, Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis and Dicrocoelium dendriticum [27][28][29]. However, the majority of these studies simply detected the presence of these species through the analysis of stool samples, with few determining the physiological and immunological significance of such co-occurrences.…”
Section: Discussionmentioning
confidence: 99%